Effects of miR-204-5p modulation on PAX6 regulation and corneal inflammation - Mojdeh Abbasi; Maryam Amini; Petros Moustardas; Quirin Gutsmiedl; Dina Javidjam; Shweta Suiwal; Berthold Seitz; Fabian N. Fries; Ava Dashti; Yedizza Rautavaara; Tanja Stachon; Nóra Szentmáry; et al. (Scientific Reports, 2024)
Abstract Congenital aniridia is a rare eye disease characterized by loss of PAX6 protein leading to aniridia-associated keratopathy that significantly reduces vision. The miR-204-5p is a possible regulator of PAX6 function and here we evaluate its effect in multiple in vitro and in vivo models. In vitro, miR-204-5p overexpression suppressed vascular factor ANGPT1 in human limbal stem cells (T-LSC) and Pax6-knockdown LSC (mut-LSC), and in primary human limbal epithelial cells (LEC) at the gene and protein levels and following LPS stimulation. However, miR-204-5p inhibited VEGFA expression only in mut-LSCs and LPS-stimulated LEC. Also, miR-204-5p increased PAX6 expression in mut-LSC and differentiated corneal epithelial cells, but not in LEC. Topical miR-204-5p after LPS-induced keratitis in mice failed to suppress Vegfa, Angpt1, Il-1β, and Tnf-α or rescue Pax6 levels in contrast to in vitro results, although it significantly reduced the inflammatory infiltrate in the cornea. In Pax6 Sey/+ aniridia mice, miR-204-5p did not rescue PAX6 levels or suppress Vegfa, Angpt1, or inhibit the ERK1/2 pathway. While short-term miR-204-5p treatment effectively suppresses VEGFA and ANGPT1 and enhances PAX6 expression in multiple corneal epithelia, effects are variable across primary and immortalized cells. Effects of longer-term in vivo treatment, however, require further study.